HUBUNGAN PENERAPAN PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) DENGAN TINGKAT EKONOMI - Sefriani, Wiwit; Ekawati (Jurnal Media Ilmu Kesehatan, 2015)
Background: Pregnancy and childbirth are normal processes but can be abnormal and resulting in maternal deaths. The maternal mortality rate can be lowered by applying childbirth planning and complication prevention (P4K) earlier. This program consists of childbirth attendant planning, place of childbirth planning, cost of childbirth preparation, transportation planning, childbirth companion planning and blood donors planning. Preliminary study at Puskesmas Pleret obtained 4 of 6 pregnant women (66.67%) had not implemented P4K due to lack of financial support. The economic level affects the selection of the referral place of childbirth. Objective: To determine the relationship between the economic level and the implementation of P4K in pregnant women at Puskesmas Pleret Bantul. Methods: This study used a cross-sectional observational analytic design with a quantitative approach. The population were 106 pregnant women and samples were purposively chosen, consisted of 50 pregnant women at Puskesmas Pleret Bantu. The instrument of data collection was a questionnaire. Data were analysed with chi-square. Results: Chi Square test revealed X2 (2, n=50) =  19.659, >  X2  table  (9.21),  that  i n d i c a t e d  there  was a relationship between economic level with the implementation of P4K in pregnant women. Conclusion: The majority of pregnant women at Puskesmas Pleret  Bantul  had  low economic level and had not implemented P4K. Keywords: Economic level, childbirth planning and complications prevention program